Equal Splits or Product Prices: An Experiment - Håkan J. Holm; Emma Svensson (Lund University, School of Economics and Management, Department of Economics, 2013)
This paper compares the choice of focal points in a Nash Demand Game embedded in an abstract frame with the corresponding choices in a game with a real product frame where parties bargain for a well-known consumer product. We find that the frame has a substantial impact on the fraction of subjects choosing the equal split outcome casting doubt on the robustness of this solution in bargaining over real goods. The paper shows that there is notable heterogeneity among subjects with regard to their choices of focal points and reports individual characteristics predicting these choices.
Keywords: C91; D03; D84; 330; focal points; Nash Demand Game; heterogeneity; framing; equilibrium selection